Impact of trastuzumab on wound healing in experimental glaucoma surgery - Turgut, Burak; Eren, Kenan; Akin, Mehmet M.; Can, Nagehan Bilir; Demir, Tamer (Wiley, 2015)
BackgroundTo investigate the effects of subconjunctivally administered trastuzumab on wound healing in experimental glaucoma filtration surgery. DesignComparative, experimental study. SamplesTwenty eight eyes. MethodsTwenty-eight male New Zealand white rabbits were randomly assigned to four groups, each including seven rabbits: The rabbits in the control group were not operated on and did not receive any treatment. The rabbits in the sham group underwent trabeculectomy and had one drop of saline instilled four times a day for 14 days. The rabbits in the mitomycin-C group underwent trabeculectomy, and a sponge soaked in 0.4mg/mL mitomycin-C was applied intraoperatively to the scleral surgical site for 3min. The rabbits in the trastuzumab group underwent trabeculectomy and were injected subconjunctivally once with 1.2mg/0.1mL of the drug. On day 14 of the experiment, the operated and control eyes were enucleated and immunohistochemically analyzed. Main Outcome MeasuresMean values of fibroblast, mononuclear cell and immunostaining intensities of the transforming growth factor-, fibroblast growth factor-, and platelet derived growth factor. ResultsThe mean cell numbers and immunostaining intensities in the sham group were higher than those of the control group (P<0.01). The mean cell numbers and immunostaining intensities in the mitomycin-C group and trastuzumab group were statistically significantly lower than those of the sham group (P<0.01) while mean cell numbers and immunostaining intensities in the mitomycin-C group and trastuzumab group were similar (P>0.05). ConclusionSubconjunctival trastuzumab injection effectively suppressed subconjunctival scarring after experimental glaucoma filtration surgery.
Keywords: animal model; glaucoma; mitomycin; trabeculectomy; trastuzumab